INTERNATIONAL FORUM OF AMERICAN SOCIETY FOR ENGINEERING EDUCATION - Vasily Ivanov; Yulia Ziyatdinova (Высшее образование в России, 2016)
The paper describesthe experience of American Society for Engineering Education (ASEE) to host annual conferences and international forums where representatives of different countries of the world participate. The paper gives a comparative analysis of engineering education problems and their solutions in different countries and prospects for using the most successful international experience in Russia.Global innovative development is impossible without training competitive engineers who can create and implement groundbreaking technologies. Despite the fact that engineering education development is a national priority, it is impossible to avoid its internationalization. A number of international nonBprofit nonBgovernmental engineering education organizations aim at unitingthe faculty and administrators of engineering universities and the representativesof industry in order to develop joint solutions and improve thequality of engineering education worldBwide. The most popular of these organizations are Internationale Gesellschaft für Ingenieurpädagogik IGIP, Société Européenne pour la Formation des Ingénieurs (SEFI), Global Engineering Deans Council (GEDC), American Society for Engineering Education (ASEE), and etc.ASEE is one of the organizations implementing global scale activities. For over 120 years the society has hosted annual conferences to gather over 3,000 participants from the USA and other countries. The initiative of the last three years is the International Forum under the umbrella of these conferences. The Forum is the platform for international engineering education organizations to hold the plenary sessions where they can presentthe current state of engineering education in their countries, share their views and discuss their problems. Société Européenne pour la Formation des Ingénieurs (SEFI) and Latin American and Caribbean Consortium of Engineering Institutions (LACCEI) participated in the 2014 International Forum as partner societies and presented their views on engineering education development. The President of SEFI Kamel Hawwash gave a verydetailed report on European engineering education stressing that the global crisis that we face is the crisis in engineering competencies, which do not satisfy the requirements of the employers. The Professor of Dublin Institute of Technology Mike Murphy spoke about engineering education in Ireland under the forthcoming fusion of institutes and universities to introduce a new vision of engineering programs. The President of Global Engineering Deans Council Jose Carlos Quadrado focused on Portugal, where engineering universities are overcoming a crisis and going through restructuring aimed at training engineers capable of creating new job instead of being employed. The Executive Director of LACCEI Maria M. Larrondo Petrie gave an overview of engineering education in Latin America in the light of Vision 2025 approved in these countries. The focus in the Vision is on innovations, human resource training, and national quality infrastructure and technology development.The plenary session reports showed that the main trends in both parts of the world today are very similar. They include fusions of universities to reach new goals and enhanced collaboration with industry to develop the newly demanded programs. Another issue for the Latin American countries is the poor English language command which influences the competitiveness of the engineers. A number of measures are taken to improve the EFL teaching approaches, and they are similar to the ones in Russia. The low representation of women in science and engineering is another issue for Latin America, and LACCEI takes efforts to increase their number.The International Forumplenary sessions were followedby three tracks ofsessions: student development, faculty development and curriculum and laboratory development. Kazan National Research Technological University gave two oral reports at the faculty development track on the role of the President’s Program of training engineers in improvement of the research university educational activity and on a focused curriculum improving the written English of Russian speaking engineers.The 2014 International Forum was followed by the 121st ASEE Annual Conference to discuss different issues of engineering education. The Conference was a very large scale event, and included 2 plenary sessions, 6 distinguished lectures, 132 business meetings, around 300 technical sessions, 27 workshops, 20 poster sessions, and around 50 panel sessions. The Conference was sponsored by a number of the US and international companies, including National Instruments, NCEES, Dassault Systemes, The MathWorks, Boeing, and etc. This year, Purdue University School of Engineering and Technology, University of Notre Dame College of Engineering, Valparaiso University Engineering, Trine University, and RoseB Hulman Institute of Technology were the host institutions in Indianapolis.The main plenary session was remarkable for the National Student Award Winners recognized by the ASEE President Kenneth Galloway. The students were invited onto the stage, and short videos to introduce their achievements were shown on screens. After the plenary, the students participated in a special press conference, an outstanding experience for them. The 2014 ASEE President’s Award was given to Ioannis Miaoulis and the National Center for Technological Literacy at the Museum of Science, Boston for making a special use of print, broadcast, and electronic media to encourage KB12 students to pursue an engineering career, and to both influence public opinion and gain recognition of the critical role that engineering plays in today’s technologyBdriven society.The main plenary also featured Keynote Speaker Mitchell E. Daniels, Jr., President of Purdue University, a strong supporter of engineering education. He became President of Purdue in January 2013; in the past he was twoBterm governor of Indiana, and, earlier, he worked in the White House during Ronald Reagan’s presidency and later served as director of the Office of Management and Budget under President George W. Bush.Mitchell Daniels spoke about history of Purdue as the university to teach agriculture and the mechanic arts. These competencies are still very important nowadays. In the world driven by technical innovations, the system of engineering education is facing criticism, challenges, and new competitors. There are new questions which were never asked until the last 10 years regarding the large numbers of college students, the poor skills they obtain, the real value of their diplomas. Today, engineering education is at the time of testing which requires innovative approaches to answer the questions of what to teach, how to teach and to whom we teach. Purdue answers the latter question by freezing the tuition fee for the next two years so that the most talented young people could afford studying there. In terms of how to teach, Purdue promotes new modes of teaching and transforms the majority of courses into hybrid teaching. In terms of what to teach, Purdue produces more STEM graduates than many other US universities. Moreover, they are expanding the Engineering College, as these programs are most needed and valuable. The experience of China and India shows that when young people see the centrality of engineering skills, the individual and the societal success grows.Mitchell Daniels believes that the USA need 10,000 more engineering graduates annually. And even if the country outruns the market’s need for engineers, this will be a good outcome, because the engineering mentality will take amore prominent place in the nation. The keynote speech of Mitchell Daniels was followed by a number of questions from the audience, showing a good feedback.The following three days of the Conference were very intensive in business meetings, technical sessions and other events. Kazan National Research Technological University presented an oral report on an integrated university/industry program of improving Russian industrial trainers at continuing professional development division technical session.The lastday ofthe Conference was remarkable for the ASEE International Council meeting which gathered the representatives of different international societies to discussthe prospects of collaboration with ASEE. The preliminary arrangements were made about the possible participation of Kazan National Research Technological University and National Research Tomsk Polytechnic University in the 2015 International Forum to represent the partner society, Association for Engineering Education of Russia.